Distinguishing between Contact and Administration of Heroin from a Single Fingerprint using High Resolution Mass Spectrometry. Issue 3 (4th November 2019) - Costa, Catia; Ismail, Mahado; Stevenson, Derek; Gibson, Brian; Webb, Roger; Bailey, Melanie
Abstract: Fingerprints have been proposed as a promising new matrix for drug testing. In previous work it has been shown that a fingerprint can be used to distinguish between drug users and nonusers. Herein, we look at the possibility of using a fingerprint to distinguish between dermal contact and administration of heroin. Fingerprint samples were collected from (i) 10 patients attending a drug rehabilitation clinic, (ii) 50 nondrug users and (iii) participants who touched 2 mg street heroin, before and after various hand cleaning procedures. Oral fluid was also taken from the patients. All samples were analyzed using a liquid chromatography—high resolution mass spectrometry method validated in previous work for heroin and 6-AM. The HRMS data were analyzed retrospectively for morphine, codeine, 6-acetylcodeine and noscapine. Heroin and 6-AM were detected in all fingerprint samples produced from contact with heroin, even after hand washing. In contrast, morphine, acetylcodeine and noscapine were successfully removed after hand washing. In patient samples, the detection of morphine, noscapine and acetylcodeine (alongside heroin and 6-AM) gave a closer agreement to patient testimony on whether they had recently used heroin than the detection of heroin and 6-AM alone. This research highlights the importance of washing hands prior to donating a fingerprint sample to distinguish recent contact with heroin from heroin use.